Insight into the mechanism of digestibility inhibition by interaction between corn starch with different gelatinization degree and water extractable arabinoxylan - Hong, Jing; Chen, Peixia; Liang, Xiaohui; Liu, Chong; Guan, Erqi; Omer, Saeed Hamid Saeed; Zheng, Xueling (International journal of biological macromolecules, 2024)
On the basis of revealing the interaction mechanism between corn starch (CS) and water-extractable arabinoxylan (WEAX) with high/low molecular weight (H-WEAX, L-WEAX), the degree of gelatinization (DG) on structural behaviors and in vitro digestibility of CS-WEAX complexes (CS/H, CS/L) was evaluated. With the increased DG from 50 % to 95 %, the water adsorption capacity of CS/L was increased 64 %, 58 %, 47 %, which were higher than that of CS/H (39 %, 54 %, 33 %). The gelatinization of starch was inhibited by WEAX, resulting in the enhancement of crystallinity, short-range ordered structure and molecular size of CS-WEAX complexes. Stronger interaction was detected in CS/L than with CS/H as proved by the increased hydrogen bonds and electrostatic force. Complexes exhibited higher resistant starch content (RS) at diverse DG, especially for CS/L. Notability, RS content of samples with 50 % DG were increased from 27.72 % to 32.89 % (CS/H), 36.96 % (CS/L). Except for the reduction of gelatinization degree by adding WEAX, the other possible mechanisms of retarding digestibility were explained as the small steric hindrance of L-WEAX promoted encapsulation of starch granules, limiting enzyme accessibility. Additionally, the fragmentation of CS granules with high DG promoted the movement of H-WEAX, reducing the difference in digestibility compared to CS/L. [Display omitted] •The addition of WEAX obviously reduced the in vitro digestibility of CS.•The RS content of WEAX-starch complexes was obviously enhanced for starch with 50 % DG.•L-WEAX could retain higher crystallinity, short-range ordered structure of starch.•G5-CS/L exhibited stronger hydrogen bonds and electrostatic force.•The spatial hindrance of H-WEAX decreased at high DG level.